Sir Robert Peel : statesmanship, power and party - Evans, Eric J., 1945- (Routledge, 2006)
Eric Evans presents an introduction to the life and career of British Prime Minister, Sir Robert Peel. The author reassesses Peel's career, arguing that although his executive and administrative strengths were great, he presented political problems which he was incapable of solving.
Keywords: Peel, Robert, -- 1788-1850.; Conservative Party (Great Britain) -- History -- 19th century.; Peel, Robert, -- 1788-1850; Conservative Party (Great Britain); Prime ministers -- Great Britain -- Biography.; Great Britain -- Politics and government -- 1837-1901.; Great Britain -- Politics and government -- 1830-1837.; Grande-Bretagne -- Politique et gouvernement -- 1837-1901.; Grande-Bretagne -- Politique et gouvernement -- 1830-1837.; BIOGRAPHY & AUTOBIOGRAPHY -- Historical.; HISTORY.; Politics and government; Prime ministers; Great Britain; 1800-1901; Electronic books.; Biographies; History